Effect Of Quadruple P-Spiral Split Ring Resonator (QPS-SRR) Structure On Microstrip Patch Antenna Design - Hassan, Nornikman; Abd. Aziz, Mohamad Zoinol Abidin; Noor Azizi, Muhammad Syafiq; Ramli, Mohamad Hafize; Othman, Mohd Azlishah; Sulaiman, Hamzah Asyrani; Ahmad, Badrul Hisham; Sulaiman, Mohd Hafiz (Penerbit UTM Press, 2016)
In this project, the different locations of the quadruple P-spiral split ring resonator (MI-SRR) structure are embedded in the basic rectangular patch antenna. It started with a basic rectangular microstrip patch antenna that simulated in CST Microwave Studio software. After that, four different locations (Location A, Location B, Location C and Location D) of QPS-SRR had chosen to compare its performance of return loss, resonant frequency, surface current radiation pattern, and gain. Location A is representing the antenna with the QPS-SRR at the center part of the patch while Location B has the QPS-SRR at the upper part of the FR-4 substrate. For the Location C and Location D represent the antenna with MI-SRR at the ground at antenna with MI-SRR at the other layer, respectively. Compared with the basic rectangular antenna with only – 27.082 dB, the best return loss was reached by Location A with - 34.199 dB with resonant frequency at 2.390 GHz, while the Location C only shifted the minor value to 2.394 GHz with only - 25.13 dB.